2021
DOI: 10.1002/path.5834
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of cell‐of‐origin epigenetic characteristics in non‐functional pancreatic neuroendocrine tumors

Abstract: Primary non-functional pancreatic neuroendocrine tumors (NF-PanNETs) are a heterogeneous group of neuroendocrine neoplasms that display highly variable clinical behavior. Therefore, NF-PanNETs often present clinical teams with a dilemma: the uncertain metastatic potential of the tumor has to be weighed against the morbidity associated with surgical resection. Thus, rather than utilizing current radiologic thresholds, there is an urgent need for improved prognostic biomarkers. Recent studies aimed at understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 52 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Epigenetic or transcriptomic signatures have been used to classify non-functioning pancreatic NETs based on endocrine cell type differentiation [82][83][84][85][86]. These studies have revealed three epigenetic subtypes (Table 4) resembling A (alpha) or B (beta) cells, enriched for specific structural alterations and mutational profiles, and with prognostic relevance [86]; PDX1 and ARX were found to be useful surrogate immunohistochemical markers to distinguish these tumor subtypes [83]. One group resembles B cells, without copy number alterations, MEN1 or ATRX/DAXX mutations (therefore no resulting alternative lengthening of telomeres (ALT)), and a favorable prognosis.…”
Section: What Are Functional Imaging Studies In Neuroendocrine Neopla...mentioning
confidence: 99%
“…Epigenetic or transcriptomic signatures have been used to classify non-functioning pancreatic NETs based on endocrine cell type differentiation [82][83][84][85][86]. These studies have revealed three epigenetic subtypes (Table 4) resembling A (alpha) or B (beta) cells, enriched for specific structural alterations and mutational profiles, and with prognostic relevance [86]; PDX1 and ARX were found to be useful surrogate immunohistochemical markers to distinguish these tumor subtypes [83]. One group resembles B cells, without copy number alterations, MEN1 or ATRX/DAXX mutations (therefore no resulting alternative lengthening of telomeres (ALT)), and a favorable prognosis.…”
Section: What Are Functional Imaging Studies In Neuroendocrine Neopla...mentioning
confidence: 99%
“…In summary, based on the presented data [ 9 , 19 , 41 , 42 , 44 , 71 , 82 ], at least five groups of PanNENs can be identified as they differ by cell of origin, clinical features, genetic, and epigenetic background ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these indolent neoplasms differ from the other subgroups in terms of their genetic background [ 9 ]. In contrast, PanNEN 4 resembles more likely to α cells, one theory suggesting that they probably existed as a NF-PanNET before developing functional features [ 42 ]. The last subtype refers to a proliferative group proposed by Kevin Yang et al [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations